Deleuze's philosophical heritage - Jones, Graham (Lecturer in media, communications and writing); Roffe, Jon (Edinburgh University Press, 2009)
The philosophy of Gilles Deleuze is increasingly gaining the prestige that its astonishing inventiveness calls for in the Anglo-American theoretical context. His wide-ranging works on the history of philosophy, cinema, painting, literature and politics are being taken up and put to work across disciplinary divides and in interesting and surprising ways. However, the backbone of Deleuze's philosophy - the many and varied sources from which he draws the material for his conceptual innovation - has until now remained relatively obscure and unexplored. This book takes as its goal the examination of this rich theoretical background. Presenting essays by a range of the world's foremost Deleuze scholars, and a number of up and coming theorists of his work, the book is composed of in-depth analyses of the key figures in Deleuze's lineage whose significance - as a result of either their obscurity or the complexity of their place in the Deleuzean text - has not previously been well understood. This work will prove indispensable to students and scholars seeking to understand the context from which Deleuze's ideas emerge. Included are essays on Deleuze's relationship to figures as varied as Marx, Simondon, Wronski, Hegel, Hume, Maimon, Ruyer, Kant, Heidegger, Husserl, Reimann, Leibniz, Bergson and Freud.